Studies on chloroplastic factors responsible for drought tolerance in rubber plants (Hevea brasiliensis) - Annamalainathan K; Heazlewood J L; Jacob J (Placrosym XVII, 2006, Kochi, India. Journal of Plantation Crops, 34 (3). Indian Cardamom Research Institute (Spices Board), Idukki, India, pp.643-649.)
Four clones of natural rubber plants (clone RRII 105, RRIM 600, GT 1 and PR 255) were grown in large poly bags under three different light conditions namely, 100, 70 and 30;sunlight. One set of plants was drought stressed for three weeks by withholding irrigation during the rain free summer and a second set was kept as irrigated controls at all light levels. The malondialdehyde (MDA)/chlorophyll ratio in drought affected plants was determined as an indicator of drought tolerance/susceptibility. Photosynthetic oxygen evolution rate was measured at different light intensities (LED). High light grown plants responded to measurement light intensity better than low light grown plants in the relatively stress tolerant clone RRIM 600. The apparent quantum yield of oxygen evolution and light compensation point were lesser in the low light grown plants than the open light plants. The degree of drought mediated inhibition in photosynthetic O2 evolution was lower in low light grown plants than open light plants indicating protection from photoinhibition in shaded plants. The analysis of chloroplast protein profile showed that the sun exposed plants with concomitant drought stress induced a novel 23 kDa chloroplast stress protein. LC/MSMS analysis revealed that the protein eas a small chloroplast heat shock protein (sHSP). These findings indicate that the sHPSs may play a role in drought tolerance as the more tolerant clones expresed relatively increased amounts of this protein.
Keywords: Drought; Light; Photosynthesis; Small chloroplast heat shock proteins (sHSP)